2012
DOI: 10.1073/pnas.1215928109
|View full text |Cite
|
Sign up to set email alerts
|

T-cell receptor (TCR) interaction with peptides that mimic nickel offers insight into nickel contact allergy

Abstract: T cell-mediated allergy to Ni++ is one of the most common forms of allergic contact dermatitis, but how the T-cell receptor (TCR) recognizes Ni ++ is unknown. We studied a TCR from an allergic patient that recognizes Ni ++ bound to the MHCII molecule DR52c containing an unknown self-peptide. We identified mimotope peptides that can replace both the self-peptide and Ni ++ in this ligand. They share a p7 lysine whose εNH 2 group is surface-exposed when bound to DR52c. Whereas the TCR uses germ-line complementary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 34 publications
(39 reference statements)
0
56
2
1
Order By: Relevance
“…This difference was explained by the TCR footprint being dominated by the TCRb chain and b1 a-helix residues of HLA-DP2. Yin et al also reported CDR3b had a major role in recognition of human Nickel-self natural ligand [46]. In contrast with these reports, we observed diverse CDR3b sequences in Cr-induced ACD mice.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This difference was explained by the TCR footprint being dominated by the TCRb chain and b1 a-helix residues of HLA-DP2. Yin et al also reported CDR3b had a major role in recognition of human Nickel-self natural ligand [46]. In contrast with these reports, we observed diverse CDR3b sequences in Cr-induced ACD mice.…”
Section: Discussioncontrasting
confidence: 56%
“…It was reported that activation of Ni-specific SE9 T cells depended on Thr residues in CDR1a and CDR3a [47]. Also, Ni-specific ANi2.3 interactions depended on Tyr and Thr residues in CDR1a and a Phe residue in CDR2a, and that ANi2.3 has an Arg-Asp-Gly-Tyr (RDGY) motif in CDR3b [46]. In this study, we did not identify a motif for Crbinding in CDR3a of VA11-1 but interestingly, shared TCR clonotypes contained Glu, Thr, His, Arg, and Tyr residues that have the potential to interact with Cr ions.…”
Section: Discussionmentioning
confidence: 99%
“…In the unidentified endogenous peptide associated with nickel allergy, a bound Ni 2+ ion may replace the ε-NH 2 group. From Yin et al [74]. …”
Section: Discussionmentioning
confidence: 99%
“…It is generally thought that the metal ion is bound to a self-peptide presented by an MHC molecule. The CD4 + T cell, ANi2.3, contains a Vβ17 region that is over-represented in patients suffering from severe Ni contact hypersensitivity [74]. ANi2.3 αβTCR reacts with Ni 2+ in the context of an unknown self-peptide bound to an MHC class II molecule, HLA-DR52c.…”
Section: Metal Ion Recognitionmentioning
confidence: 99%
See 1 more Smart Citation